Image of Presenter of Political Talk Show: on Problem of Gender Peculiarities - O. A. Mikhaylova; Y. S. Kharitonova (Научный диалог)
The study is done within actual direction of modern science - the gender linguistics. The article is devoted to the question of the communicative image of the TV presenters of political talk-show Vladimir Solovyov and Olga Skabeyeva. The results of a comparative analysis of the components of the public image of each media person are presented: appearance, communicative behavior, speech manners. It is shown that Solovyov and Skabeyeva have a bright, catchy, wistful image, and their similarities - leading position, business style in clothes, gestures system, categoricalness - are determined by the program format. It is proved that at the same time, communicative images of the presenters have a specific gender identity: Vladimir Solovyov’s image corresponds to stereotypical idea of a real man, while Olga Skabeyeva’s image combines both typically female (modesty, elegance, parity) and male characteristics (rationality, rigidity, hardness). Special attention is given to verbal behaviour that detects the individual characteristics of each media person. Vladimir Solovyov’s manner of speech can be characterized as assertive, poly-stylistic, management one. The authors argue that the dominant for this presenter is a strategy of self-presentation, while the main intention can be defined as the retention of communicative leadership. The general speech style of Olga Skabeyeva can be described as aggressive, but the presenter purely uses female methods of mitigating the conflict. It is proved that the communicative style of the presenter is not free from gender peculiarities of the personality.